1990
DOI: 10.1523/jneurosci.10-04-01082.1990
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic factors influencing properties and growth patterns of identified leech neurons in culture

Abstract: An analysis has been made of intrinsic mechanisms influencing growth patterns of 2 identified leech interneurons in tissue culture. These small cells (known as DL and VL) display unusual arborizations in the ganglion. The distinctive branching patterns resemble the letter "T" for VL and the letter "Y" for DL. DL and VL cells contain serotonin and can be identified in situ with Neutral red. 1. DL and VL cells were isolated and cultured on 2 homogeneous substrates, concanavalin A (Con A) and leech extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 22 publications
1
22
2
Order By: Relevance
“…Additional techniques for cell manipulations will be required in further investigations of this notion. However, our result is consistent with previous observations in dissociated cultures of mammalian hippocampal and cortical neurons (Kriegstein and Dichter, 1983;Bartlett and Banker, 1984) and of identified invertebrate neurons (Hadley et al, 1985;Acklin and Nicholls, 1990) that intrinsic factors play an important role in determining the basic features of nerve cells such as the number of primary projections.…”
Section: B Multipolarsupporting
confidence: 93%
See 1 more Smart Citation
“…Additional techniques for cell manipulations will be required in further investigations of this notion. However, our result is consistent with previous observations in dissociated cultures of mammalian hippocampal and cortical neurons (Kriegstein and Dichter, 1983;Bartlett and Banker, 1984) and of identified invertebrate neurons (Hadley et al, 1985;Acklin and Nicholls, 1990) that intrinsic factors play an important role in determining the basic features of nerve cells such as the number of primary projections.…”
Section: B Multipolarsupporting
confidence: 93%
“…The general morphology, such as arborization patterns of DrosopIzila nerve cells, are rather stable in culture (Kim and Wu. 1987) as has been shown in other organisms (Bray, Bunge, and Chapman, 1987;Acklin and Nicholls, 1990). Once primary neurites are differentiated, further development of Drosophilu neurons in culture involves mainly elaboration of primary processes (Kim and Wu.…”
Section: Introductionmentioning
confidence: 71%
“…While Our present experiments do not rule out intrinsically controlled recapitulation of branching pattern, these peripheral axons had aligned longitudinally in a trajectory that would direct them toward the cut ends of intact heart tube several segments away. Other leech neurons have been shown to be capable of recapitulating major branch points in vitro (Acklin and Nicholls, 1990) and HEs may well be similarly restricted to generate a particular type or number of branch points. Our present results are also consistent with the idea that the intact heart muscle exerts a trophic or tropic influence over HE growth cones from some distance.…”
mentioning
confidence: 99%
“…The same cells reproduce these patterns in culture. Disruption of the microtubular array does not affect the ability of the cell to regrow in a bipolar fashion ( Acklin and Nicholls, 1990). These results have shown that substrate molecules are of critical importance for inducing the growth of leech nerve cells, and that it is actually the local interaction between the substrate and the neurites that determines the pattern of outgrowth.…”
Section: Growth Of Leech Nerve Cells In Culture Depends On the Substratementioning
confidence: 78%